Plasma etching process for aluminum-copper metallization by photoresist margin improvement for CMOS 0.13-µm technology - Mohamed Hassan, Wan Faizal (2022)
In wafer fabrication manufacturing, the aluminum etching process is a dry plasma etching process used as the main process for construction of aluminum copper (AlCu) interconnect structures. As customer requirements changed for faster, more reliable and lower cost chips, chip manufacturers have learned to reduce the size of components on a chip in order to achieve those requirements. As the geometry of the chip is getting smaller, the width of AlCu line wiring specifications is also shrinking. To print the smaller geometry pattern requirements, the photoresist (PR) thickness in the masking process also has to be reduced for better resolution. Such a thinner resist will create a challenge during plasma etching to ensure a minimal resist loss process which will require a new type of equipment. The use of an oxide film as a hard mask has been evaluated by many other researchers. This approach does require a process integration change with full technology qualifications and will easily take many lengthy qualification procedures particularly to qualify the existing products. In SilTerra, the plasma AlCu etching process for 0.13µm High Voltage (HV) technology is qualified at the Applied Material (AMAT) DPS+ etcher system. Larger chamber volume design coupled with the use of C2H4 patterned passivation gas process is enabling the 0.13µm AlCu etching process to run with enough PR margin process. This limited capacity of the AMAT tools triggered SilTerra engineers to initiate process qualification works at the LAM9600PTX chamber which is an equipment designed for 0.16µm and bigger technology scale. The initial trial using SilTerra 0.13µm technology process failed to meet the process requirements on the PR remaining thickness. The insufficient margin caused deformed AlCu structure formations. This thesis evaluated the use of methane gas during AlCu etching process as an additional passivation gas to the existing nitrogen gas. The AlCu etching rate non-uniformity due to aspect ratio dependent etching (ARDE) is evaluated at a methane gas flow rate within the range of 0 to 18 standard cubic centimeters per minute (SCCM). One factor of a time experiment with comprehensive design of experiment trials is evaluated and it is found that, an addition of methane at 9 SCCM in AlCu etching step able to reduce the ARDE% from 26% to 21% with acceptable incremental of metal width critical dimension. A 60 SCCM of Cl2 and 10 SCCM of CHF3 gas mixture has been determined from DOE runs as a replacement gas mixture to the existing Cl2/O2 to address organic backside anti- refractive coating (OBARC) etching requirement for lower PR loss process. The true mean value of PR margin thickness and oxide loss margin thickness from the proposed new process conditions have been statistically determined to meet the minimum SilTerra process requirement. The electrical tests on M2B_V and RS_M2C parameters are verified on the production pre-runs and the final sort yield data are validated on the volume runs successfully. This novelty finding is successfully increasing the capacity with an additional 5,000 wafers output per month which is equivalent to USD 2.5 million and a capital expenditure avoidance of USD 5 million.